2016
DOI: 10.1002/2016gl069298
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol data assimilation using data from Himawari‐8, a next‐generation geostationary meteorological satellite

Abstract: Himawari‐8, a next‐generation geostationary meteorological satellite, was launched on 7 October 2014 and became operational on 7 July 2015. The advanced imager on board Himawari‐8 is equipped with 16 observational bands (including three visible and three near‐infrared bands) that enable retrieval of full‐disk aerosol optical properties at 10 min intervals from geostationary (GEO) orbit. Here we show the first application of aerosol optical properties (AOPs) derived from Himawari‐8 data to aerosol data assimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 41 publications
0
92
0
Order By: Relevance
“…The center of Himawari-8 is 140.7 • E over equator, and the observation area is located from 80 • E to 160 • W and from 60 • N to 60 • S [28]. Himawari-8 can provide AODs at 500 nm and Ångström exponents with 10 min intervals and 5 km coverage over about one-third of the Earth (i.e., Western Pacific Ocean, East and Southeast Asia, and Oceania) [25,26]. The AODs were subjected to quality assurance with four confidence levels, namely, "very good," "good," "marginal," and "no confidence" (or "no retrieval").…”
Section: Datasetsmentioning
confidence: 99%
“…The center of Himawari-8 is 140.7 • E over equator, and the observation area is located from 80 • E to 160 • W and from 60 • N to 60 • S [28]. Himawari-8 can provide AODs at 500 nm and Ångström exponents with 10 min intervals and 5 km coverage over about one-third of the Earth (i.e., Western Pacific Ocean, East and Southeast Asia, and Oceania) [25,26]. The AODs were subjected to quality assurance with four confidence levels, namely, "very good," "good," "marginal," and "no confidence" (or "no retrieval").…”
Section: Datasetsmentioning
confidence: 99%
“…Himawari-8 is the next-generation geostationary meteorological satellite [25,26]. The observational bands in visible and near-infrared wavelengths of Himawari-8 are sensitive to aerosol scattering and absorption, which is an attractive characteristic for aerosol research.…”
Section: Introductionmentioning
confidence: 99%
“…The AHI is equipped with 16 observational bands from visible to infrared with a spatial resolution of 0.5-2 km and temporal resolution of 10 min (six full-disk images per hour) [26,29]. images per hour) [26,29]. Table 1 shows the detailed spectral bands of AHI (source: http://www.jmanet.go.jp/msc/en/), and their corresponding channel response functions are plotted in Figure 1.…”
Section: Himawari-8 Advanced Himawari Imager (Ahi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al: Improving PM 2.5 forecast over China et al, 2010a, b;Pagowski and Grell, 2012;Dai et al, 2014;Rubin et al, 2016;Ying et al, 2016;Yumimoto et al, 2016) and the hybrid variational-ensemble DA approach (Schwartz et al, 2014) have also been applied to aerosol predictions. All these studies have shown that DA is one of the most effective ways of improving aerosol forecasting through assimilating aerosol observations from multiple sources (e.g.…”
Section: Introductionmentioning
confidence: 99%